Kidney failure: aims for the next 10 years and barriers to success - Remuzzi, Giuseppe; Benigni, Ariela; Finkelstein, Fredric O; Grunfeld, Jean-Pierre; Joly, Dominique; Katz, Ivor; Liu, Zhi-Hong; Miyata, Toshio; Perico, Norberto; Rodriguez-Iturbe, Bernardo; Antiga, Luca; Schaefer, Franz; et al. (The lancet, 2013)
Although in some parts of the world acute and chronic kidney diseases are preventable or treatable disorders, in many other regions these diseases are left without any care. The nephrology community needs to commit itself to reduction of this divide between high-income and low-income regions. Moreover, new and exciting developments in fields such as pharmacology, genetic, or bioengineering, can give a boost, in the next decade, to a new era of diagnosis and treatment of kidney diseases, which should be made available to more patients.
Gesehen am 10.01.2022